Permeable mortar based on building waste composite phosphogypsum and preparation method thereof
Through modified recycled aggregate and microcapsule technology, the problems of early hydration and poor durability of permeable mortars are solved, and high permeability, high strength and durability are achieved, which promotes the resource utilization of phosphogypsum and construction waste, and improves paving quality and road structure stability.
Patent Information
- Application Number
- CN202510412048.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2025-07-04
AI Technical Summary
The existing permeable mortar has the problems of early hydration and short settling time, which leads to insufficient strength and poor durability in the later stage. At the same time, the application rate of phosphogypsum and construction waste in conventional mortar systems is low, causing environmental pollution.
Modified regenerated aggregate and microcapsule technology are used to treat regenerated aggregates through pickling and surfactant, and the controlled release design of sodium metasilicate and aluminum sulfate is combined to form microcapsules, optimize the microstructure, promote the uniform distribution of C-S-H gel and ettringite, extend the settling time, and improve mechanical strength and durability.
Prepare water-permeable, high-strength and high durability permeable mortar to extend the condensation time, reduce production costs, realize the resource utilization of phosphogypsum and construction waste, and improve paving quality and road structure stability.
Smart Images

Figure BDA0005342837650000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of building materials, and particularly relates to a permeable mortar based on construction waste and composite phosphogypsum and a preparation method thereof. Background Art
[0002] A permeable ground is an excellent auxiliary material that can protect groundwater, maintain ecological balance, and alleviate the urban heat island effect. It is of special significance for the healthy development of the human living environment, urban rainwater management, and water pollution prevention and control. However, the proportion of impermeable ground in many domestic cities has exceeded 70%, changing the original permeability property of the natural ground and greatly damaging the ecological environment. Especially in cities with more rainfall, if the ground is paved with non-permeable materials such as cement, asphalt, and marble, during rain, the impermeable ground completely prevents rainwater from directly penetrating into the ground, and the accumulated water on the ground makes people's travel very inconvenient. At the same time, it also causes a waste of precious water resources, increases the burden on urban drainage facilities, and the large loss of rainwater further exacerbates the urban drought and water shortage problems. In addition, the existing permeable concrete has poor mechanical properties and durability during use. Therefore, improving the quality of the permeable mortar of permeable concrete to solve the problems of permeable concrete has become an important research direction.
[0003] In view of the above problems, the invention patent CN102010178B discloses a bubble lightweight concrete interfacial agent mortar composition and a construction method thereof. The composition includes the following components in parts by weight: 30-50 parts of ordinary Portland cement, 10-30 parts of sulfoaluminate cement, 1-3 parts of potassium alum, 5-10 parts of floor mortar latex powder, 3-6 parts of zinc fluorosilicate, 0.5-1.5 parts of sodium fluorosilicate, 4-8 parts of sodium silicate, 5-10 parts of calcium hydroxide, 3-6 parts of sodium carbonate, and 3-6 parts of sodium petroleum sulfonate. In this method, silicate and potassium alum will accelerate the early hydration of the cementitious material during the hydration reaction. However, directly adding them to the raw material system will cause a rapid hydration reaction during the mixing stage, resulting in premature dissipation of active substances and ultimately a decrease in later strength. In addition, the too-fast hydration reaction will shorten the setting time, thus affecting the construction performance. The invention patent CN108328966B discloses a permeable mortar for a sponge city and a preparation method thereof. The permeable mortar includes slag, silica fume, crushed pebbles, and a strengthening agent. Although this method solves the permeable problem to a certain extent, its mechanical properties and durability are poor and cannot meet the high requirements of the current rapid development.
[0004] Phosphogypsum is a solid waste discharged from industrial production of phosphoric acid or phosphate fertilizer. China is the largest producer of phosphoric acid and phosphate fertilizer in the world. With the rapid development of the phosphate fertilizer industry, the discharge of phosphogypsum has also shown an increasing trend year by year. So far, the stockpile of phosphogypsum in China has exceeded 300 million tons, and the annual production will exceed 70 million tons. Existing research has proved that phosphogypsum can be used as a soil conditioner, building gypsum, and road filling material. However, the comprehensive utilization rate of phosphogypsum is still less than 40%. Calcium sulfate contained in phosphogypsum has active hydration potential, but its utilization rate in the conventional mortar system is low. With the continuous development of urban construction, the consumption of concrete materials is increasing. The amount of waste concrete demolished every year, the waste concrete generated by newly built buildings, and the waste concrete discharged by concrete factories and precast component factories is huge. With the continuous increase of construction waste, the recycling of recycled aggregates has become an important direction for energy conservation and environmental protection. However, waste recycled aggregates usually have residual cement on the surface, microcracks, and attached impurities, and direct application is likely to lead to insufficient mortar strength and durability problems. Summary of the Invention
[0005] Aiming at the deficiencies of the above-mentioned prior art, the technical problem to be solved by the present invention is: how to provide a permeable mortar based on construction waste composite phosphogypsum and its preparation method to solve the problems existing in the existing mortar materials, such as early hydration, short setting time, resulting in insufficient later strength and poor durability, as well as environmental pollution caused by a large amount of accumulation of phosphogypsum and construction waste, and low application rate in the conventional mortar system.
[0006] To solve the above technical problems, the present invention adopts the following technical solution: A permeable mortar based on construction waste composite phosphogypsum, comprising the following raw materials in parts by weight: 4 - 8 parts of 1.18 - 2.36 mm modified recycled aggregates, 16 - 22 parts of 2.36 - 4.75 mm modified recycled aggregates, 2 - 4 parts of cement, 2 - 4 parts of phosphogypsum, 2 - 3 parts of water, 3 - 5 parts of microcapsules, and 1 part of water reducer;
[0007] The modified recycled aggregates are obtained by crushing and screening construction waste, then pickling and treating with a surfactant, and then washing, drying, and screening to the target particle size; in this way, the surface of the recycled aggregates is smoother after modification, reducing microcracks, improving the wrapping of the paste, and after screening and surface coating, the particle gradation of the aggregates is optimized and the pore structure is more stable. These changes can enable the aggregates to reduce excessive water absorption, improve the fluidity of the mortar, ensure uniform hydration, and at the same time make the internal pores of the mortar more uniform, ensuring good water permeability.
[0008] The microcapsules have sodium metasilicate and aluminum sulfate as the core and polyvinyl alcohol, chitosan or sodium alginate as the wall. In this way, the water solubility of polyvinyl alcohol / chitosan / sodium alginate varies with the molecular weight and degree of decomposition, and the dissolution rate can be adjusted, so that the controlled release design of the core material can be achieved. Moreover, the coating layer of polyvinyl alcohol / chitosan / sodium alginate in the aqueous phase is relatively uniform, ensuring the stability of the microcapsule structure during the hydration process. Therefore, the use of microcapsules can control the release rate of the active components in the core, ensure the gradual release of sodium metasilicate and aluminum sulfate during the curing process, and improve the modification efficiency. In addition, the microcapsules can continuously release SiO2 and Al2O3 during the curing process, promote the uniform distribution of C-S-H gel and ettringite, thereby optimizing the microstructure and improving the mechanical strength and durability. And the incorporation of the two can adjust the pH value during the hydration process, making the hydration reaction more uniform.
[0009] Specifically, after sodium metasilicate is dissolved, it can slowly release active SiO2, which can react with Ca in phosphogypsum 2+ to undergo hydration and promote the formation of C-S-H with cementing properties, enhancing the strength and durability of the permeable mortar.
[0010] Na2SiO3 + H2O → 2Na + + H2SiO3 → SiO2 + H2O
[0011] After aluminum sulfate is dissolved, it can slowly release Al(OH)3, which can further form active Al2O3 and react with phosphogypsum to promote the formation of ettringite and improve the late strength.
[0012] Al2(SO4)3 + 6H2O → 2Al(OH)3 + 3H2SO4
[0013] Preferably, the mass ratio of sodium metasilicate to aluminum sulfate is 1.5 - 2.5:1.
[0014] Preferably, the mass ratio of the core to the wall is 4 - 8:1. The molecular weight of the wall material is 80000 - 100000 Da.
[0015] Preferably, the surfactant is Tween-20 or Triton X-100; the pickling is to immerse in dilute hydrochloric acid with a concentration of 1% - 3% for 5 - 10 min.
[0016] Another object of the present invention also lies in providing a preparation method of the above-mentioned permeable mortar based on construction waste composite phosphogypsum, comprising the following steps:
[0017] 1) Crush, screen, wash, degrease and dry the construction waste to remove the residual cement slurry and impurities on the surface, and obtain recycled aggregates with uniform particle size and clean surface.
[0018] 2) Pickle the recycled aggregate obtained in step 1), then place it in a surfactant for treatment, followed by rinsing and drying. Finally, screen out two grades of aggregates with particle sizes of 1.18 - 2.36 mm and 2.36 - 4.75 mm, and the modified recycled aggregate is obtained.
[0019] 3) Dissolve the capsule wall material in deionized water, heat and stir until completely uniform to obtain a polymer solution. Then add sodium metasilicate and aluminum sulfate and stir at a low speed to make them evenly dispersed. Next, add an emulsifier under high-speed stirring to form a raw slurry containing active components. Drop the raw slurry into liquid paraffin, generate fine and uniform droplets through emulsification, and adjust the pH value of the system to 4.5 - 6.0 to cause the polymer in these droplets to crosslink and solidify, forming a stable capsule wall, thereby firmly encapsulating sodium metasilicate and aluminum sulfate. Finally, separate the microcapsules by centrifugation or filtration, wash them repeatedly to remove residual solvents and unreacted substances, and finally perform a drying treatment under low-temperature conditions to obtain a microcapsule product with good controlled-release performance, that is, the microcapsules are obtained.
[0020] 4) Weigh all raw materials by weight parts, mix them evenly to obtain a mixture, and then mold and cure the mixture to obtain the permeable mortar.
[0021] In this way, during the mixing and curing process of the permeable mortar, water gradually penetrates into the coating layer of the microcapsules. As the water penetrates, the coating material gradually swells and degrades, making the internal sodium metasilicate and aluminum sulfate in a diffusible state. After partial dissolution of the coating layer, sodium metasilicate and aluminum sulfate in the microcapsules begin to diffuse outward along the concentration gradient. As the curing time prolongs, the remaining active components in the microcapsules continue to diffuse and release, enabling the reaction to proceed step by step, avoiding the problems of local supersaturation or concentrated precipitation of hydration products caused by a one-time release, and thus solving the problems of early hydration and short setting time.
[0022] Preferably, the construction waste can be selected from one or more of waste concrete, waste bricks or waste blocks.
[0023] Preferably, in step 2), the pickling time is 5 - 10 min, the treatment time in the surfactant is 5 - 15 min, and the drying temperature is 60 - 70 °C.
[0024] Preferably, in step 3), the concentration of the polymer solution is 3 - 5 wt%; the emulsifier is Tween 80 or Span 80; the low-speed stirring speed is 300 - 500 rpm, and the high-speed stirring speed is 3000 - 4000 rpm.
[0025] Preferably, the curing in step 4) is carried out in an environment of 25 - 30 °C and a humidity of 95 - 100% for 28 - 30 d.
[0026] Another object of the present invention also lies in providing the application of the above permeable mortar or the permeable mortar prepared by the above method in the preparation of road materials.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] 1. The present invention provides a permeable mortar with high permeability, high strength, high durability, low carbon and environmental protection. The modified recycled aggregate added in the raw materials of the permeable mortar has a stable pore structure and few microcracks, which improves the wrapping property and fluidity of the mortar, ensures uniform hydration, and at the same time makes the internal pores of the mortar more uniform, ensuring good water permeability. The controlled release design of the microcapsules for the active components sodium metasilicate and aluminum sulfate ensures the continuous release of SiO2 and Al2O3 during the curing process, and through the organic combination with the hydration reaction of phosphogypsum, promotes the uniform distribution of C-S-H gel and ettringite, thereby optimizing the microstructure, improving the later mechanical strength and durability, and can extend the setting time, ensuring the construction performance. The permeable mortar prepared by the present invention has excellent water permeability, compressive strength and high durability through the synergistic effect of multi-level processes, can meet industrial requirements, can improve the paving quality of ground materials such as permeable bricks, and thus improve the overall stability and service life of the road structure.
[0029] 2. The permeable mortar prepared by the present invention uses construction waste and phosphogypsum as the main raw materials, and the raw materials are simple and easy to obtain. It not only effectively improves the resource utilization value of construction solid waste and industrial by-product gypsum, but also can significantly reduce production costs and energy consumption, provides a new technical path for the development of green building materials, realizes the reduction and resource application of phosphogypsum and construction waste, and has good application prospects. Specific Embodiments
[0030] The following further describes the present invention in detail with reference to the embodiments. It should be understood that the following embodiments are only used to illustrate and explain the present invention exemplarily, and should not be construed as limiting the protection scope of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection of the present invention. Unless otherwise specified, the raw materials and reagents used in the following embodiments are commercially available products or can be prepared by known methods.
[0031] I. A preparation method of a permeable mortar based on construction waste and composite phosphogypsum
[0032] Example 1: This example adopts the following steps:
[0033] 1) The construction waste is crushed, screened, washed, degreased and dried to remove the residual cement slurry and impurities on the surface, and recycled aggregates with uniform particle size and clean surface are obtained.
[0034] 2) The recycled aggregates obtained in step 1) are immersed in dilute hydrochloric acid with a concentration of 1% - 3% for 5 - 10 min, then the pickled recycled aggregates are treated in Tween-20 for 5 - 15 min, then rinsed with clear water and dried in an environment of 60 - 70 °C. Finally, a vibrating screen is used to screen out two grades of aggregates with particle sizes of 1.18 - 2.36 mm and 2.36 - 4.75 mm, and the modified recycled aggregates are obtained.
[0035] 3) Polyvinyl alcohol is dissolved in deionized water and heated and stirred at 70 - 80 °C until completely uniform to obtain a stable polymer solution with a concentration of 3 - 5 wt%. Then sodium metasilicate and aluminum sulfate are added to the polymer solution according to a predetermined mass ratio of 2:1, where the mass ratio of polyvinyl alcohol to sodium metasilicate and aluminum sulfate is 6:1, and stirred at a speed of 300 - 500 rpm to make it uniformly dispersed to form a raw slurry containing active components. Then, at a stirring speed of 3000 - 4000 rpm, 0.25 wt% Tween80 emulsifier is added, and the pH value of the system is adjusted to 4.5 - 6.0. The microcapsules are separated by centrifugation or filtration, and after being washed repeatedly to remove the residual solvent and unreacted substances, finally, drying treatment is carried out under low-temperature conditions to obtain a microcapsule product with good controlled-release performance, that is, microcapsules are obtained.
[0036] 4) Prepare raw materials: including the following components in parts by weight: 6 parts of 1.18 - 2.36 mm modified recycled aggregates, 20 parts of 2.36 - 4.75 mm modified recycled aggregates, 3 parts of cement, 3 parts of phosphogypsum, 2 parts of water, 4 parts of microcapsules and 1 part of water reducer.
[0037] 5) The raw materials prepared in step 4) are mixed evenly to obtain a mixture, and then the mixture is molded in a mold and cured in an environment with a temperature of 25 °C and a humidity of 95% for 28 d, and the permeable mortar is obtained.
[0038] Example 2: The following steps are adopted in this example:
[0039] 1) The construction waste is crushed, screened, washed, degreased and dried to remove the residual cement slurry and impurities on the surface, and recycled aggregates with uniform particle size and clean surface are obtained.
[0040] 2) Immerse the recycled aggregate obtained in step 1) in dilute hydrochloric acid with a concentration of 1% - 3% for 5 - 10 min, then place the pickled recycled aggregate in Tween-20 for 5 - 15 min, then rinse it with clear water and dry it in an environment of 60 - 70 °C. Finally, use a vibrating screen to screen out two grades of aggregates with particle sizes of 1.18 - 2.36 mm and 2.36 - 4.75 mm, thus obtaining the modified recycled aggregate.
[0041] 3) Dissolve polyvinyl alcohol in deionized water, heat and stir at 70 - 80 °C until completely uniform to obtain a stable polymer solution with a concentration of 3 - 5 wt%. Then add sodium metasilicate and aluminum sulfate to the polymer solution according to a predetermined mass ratio of 2.5:1, where the mass ratio of polyvinyl alcohol to sodium metasilicate and aluminum sulfate is 6:1, and stir at a speed of 300 - 500 rpm to make it uniformly dispersed to form a raw slurry containing active components. Then, at a stirring speed of 3000 - 4000 rpm, add 0.25 wt% Tween80 emulsifier and adjust the pH value of the system to 4.5 - 6.0. Separate the microcapsules by centrifugation or filtration, wash them repeatedly to remove residual solvents and unreacted substances, and finally conduct drying treatment under low-temperature conditions to obtain a microcapsule product with good controlled-release performance, that is, obtain the microcapsules.
[0042] 4) Prepare raw materials: including the following components in parts by weight: 6 parts of 1.18 - 2.36 mm modified recycled aggregate, 20 parts of 2.36 - 4.75 mm modified recycled aggregate, 3 parts of cement, 3 parts of phosphogypsum, 2 parts of water, 4 parts of microcapsules, and 1 part of water reducer.
[0043] 5) Mix the raw materials prepared in step 4) evenly to obtain a mixture, then mold the mixture in a mold and cure it in an environment with a temperature of 25 °C and a humidity of 95% for 28 d, thus obtaining the permeable mortar.
[0044] Example 3: This example adopts the following steps:
[0045] 1) Crush, screen, wash, degrease, and dry the construction waste to remove the residual cement slurry and impurities on the surface, and obtain recycled aggregates with uniform particle sizes and clean surfaces.
[0046] 2) Immerse the recycled aggregate obtained in step 1) in dilute hydrochloric acid with a concentration of 1% - 3% for 5 - 10 min, then place the pickled recycled aggregate in Tween-20 for 5 - 15 min, then rinse it with clear water and dry it in an environment of 60 - 70 °C. Finally, use a vibrating screen to screen out two grades of aggregates with particle sizes of 1.18 - 2.36 mm and 2.36 - 4.75 mm, thus obtaining the modified recycled aggregate.
[0047] 3) Dissolve polyvinyl alcohol in deionized water, heat and stir at 70 - 80 °C until completely homogeneous to obtain a stable polymer solution with a concentration of 3 - 5 wt%. Then add sodium metasilicate and aluminum sulfate into the polymer solution according to a predetermined mass ratio of 2:1, where the mass ratio of polyvinyl alcohol to sodium metasilicate and aluminum sulfate is 6:1, stir at a speed of 300 - 500 rpm to disperse them evenly to form a raw slurry containing active components. Then, at a stirring speed of 3000 - 4000 rpm, add 0.25 wt% Tween 80 emulsifier and adjust the pH value of the system to 4.5 - 6.0. Separate the microcapsules by centrifugation or filtration, wash them repeatedly to remove residual solvents and unreacted substances, and finally conduct drying treatment under low-temperature conditions to obtain a microcapsule product with good controlled-release performance, that is, obtain microcapsules.
[0048] 4) Prepare raw materials: including the following components in parts by weight: 6 parts of 1.18 - 2.36 mm modified recycled aggregate, 20 parts of 2.36 - 4.75 mm modified recycled aggregate, 3 parts of cement, 3 parts of phosphogypsum, 2 parts of water, 3 parts of microcapsules, and 1 part of water reducer.
[0049] 5) Mix the raw materials prepared in step 4) evenly to obtain a mixture, then form the mixture in a mold and cure it in an environment with a temperature of 25 °C and a humidity of 95% for 28 d to obtain the permeable mortar.
[0050] Example 4: The following steps are adopted in this example:
[0051] 1) Crush, screen, wash, degrease, and dry construction waste to remove the residual cement slurry and impurities on the surface to obtain recycled aggregate with uniform particle size and clean surface.
[0052] 2) Immerse the recycled aggregate obtained in step 1) in dilute hydrochloric acid with a concentration of 1% - 3% for 5 - 10 min, then place the pickled recycled aggregate in Tween-20 for 5 - 15 min, then rinse it with clear water and dry it in an environment of 60 - 70 °C, and finally use a vibrating screen to screen out two grades of aggregate with particle sizes of 1.18 - 2.36 mm and 2.36 - 4.75 mm, that is, obtain modified recycled aggregate.
[0053] 3) Dissolve polyvinyl alcohol in deionized water, heat and stir at 70 - 80 °C until completely homogeneous to obtain a stable polymer solution with a concentration of 3 - 5 wt%. Then add sodium metasilicate and aluminum sulfate into the polymer solution according to a predetermined mass ratio of 2:1, where the mass ratio of polyvinyl alcohol to sodium metasilicate and aluminum sulfate is 6:1, stir at a speed of 300 - 500 rpm to disperse them evenly to form a raw slurry containing active components. Then, at a stirring speed of 3000 - 4000 rpm, add 0.25 wt% Tween 80 emulsifier and adjust the pH value of the system to 4.5 - 6.0. Separate the microcapsules by centrifugation or filtration, wash them repeatedly to remove residual solvents and unreacted substances, and finally conduct drying treatment under low-temperature conditions to obtain a microcapsule product with good controlled-release performance, that is, obtain the microcapsules.
[0054] 4) Prepare raw materials: including the following components by weight: 8 parts of 1.18 - 2.36 mm modified recycled aggregate, 20 parts of 2.36 - 4.75 mm modified recycled aggregate, 3 parts of cement, 3 parts of phosphogypsum, 2 parts of water, 3 parts of microcapsules, and 1 part of water reducer.
[0055] 5) Mix the raw materials prepared in step 4) evenly to obtain a mixture, then mold the mixture in a mold and cure it in an environment with a temperature of 25 °C and a humidity of 95% for 28 d to obtain the permeable mortar.
[0056] Example 5: The following steps are adopted in this example:
[0057] 1) Crush, screen, wash, degrease, and dry construction waste to remove the residual cement slurry and impurities on the surface, and obtain recycled aggregates with uniform particle size and clean surface.
[0058] 2) Immerse the recycled aggregates obtained in step 1) in dilute hydrochloric acid with a concentration of 1% - 3% for 5 - 10 min, then place the pickled recycled aggregates in Tween-20 for 5 - 15 min, then rinse with clean water and dry in an environment of 60 - 70 °C, and finally use a vibrating screen to screen out two grades of aggregates with particle sizes of 1.18 - 2.36 mm and 2.36 - 4.75 mm, that is, obtain the modified recycled aggregates.
[0059] 3) Dissolve polyvinyl alcohol in deionized water, heat and stir at 70 - 80 °C until completely homogeneous to obtain a stable polymer solution with a concentration of 3 - 5 wt%. Then add sodium metasilicate and aluminum sulfate into the polymer solution according to a predetermined mass ratio of 2:1, where the mass ratio of polyvinyl alcohol to sodium metasilicate and aluminum sulfate is 6:1, stir at a speed of 300 - 500 rpm to disperse them evenly to form a raw slurry containing active components. Then, at a stirring speed of 3000 - 4000 rpm, add 0.25 wt% Tween 80 emulsifier and adjust the pH value of the system to 4.5 - 6.0. Separate the microcapsules by centrifugation or filtration, wash them repeatedly to remove residual solvents and unreacted substances, and finally conduct drying treatment under low-temperature conditions to obtain a microcapsule product with good controlled-release performance, that is, obtain the microcapsules.
[0060] 4) Prepare raw materials: including the following components in parts by weight: 6 parts of 1.18 - 2.36 mm modified recycled aggregate, 20 parts of 2.36 - 4.75 mm modified recycled aggregate, 3 parts of cement, 4 parts of phosphogypsum, 2 parts of water, 4 parts of microcapsules and 1 part of water reducer.
[0061] 5) Mix the raw materials prepared in step 4) evenly to obtain a mixture, then form the mixture in a mold and cure it in an environment with a temperature of 25 °C and a humidity of 95% for 28 d to obtain the permeable mortar.
[0062] Example 6: This example adopts the following steps:
[0063] 1) Crush, screen, wash, degrease and dry the construction waste to remove the residual cement slurry and impurities on the surface, and obtain recycled aggregates with uniform particle size and clean surface.
[0064] 2) Immerse the recycled aggregates obtained in step 1) in dilute hydrochloric acid with a concentration of 1% - 3% for 5 - 10 min, then place the pickled recycled aggregates in Tween-20 for 5 - 15 min, then rinse with clean water and dry in an environment of 60 - 70 °C, and finally use a vibrating screen to screen out two grades of aggregates with particle sizes of 1.18 - 2.36 mm and 2.36 - 4.75 mm, that is, obtain the modified recycled aggregates.
[0065] 3) Dissolve polyvinyl alcohol in deionized water, heat and stir at 70 - 80 °C until completely homogeneous to obtain a stable polymer solution with a concentration of 3 - 5 wt%. Then add sodium metasilicate and aluminum sulfate to the polymer solution according to a predetermined mass ratio of 2:1, where the mass ratio of polyvinyl alcohol to sodium metasilicate and aluminum sulfate is 6:1, stir at a speed of 300 - 500 rpm to disperse them evenly, and form a raw slurry containing active components. Then, at a stirring speed of 3000 - 4000 rpm, add 0.25 wt% Tween 80 emulsifier, and adjust the pH value of the system to 4.5 - 6.0. Separate the microcapsules by centrifugation or filtration, wash them repeatedly to remove residual solvents and unreacted substances, and finally conduct drying treatment under low-temperature conditions to obtain a microcapsule product with good controlled-release performance, that is, obtain microcapsules.
[0066] 4) Prepare raw materials: including the following components in parts by weight: 6 parts of 1.18 - 2.36 mm modified recycled aggregate, 20 parts of 2.36 - 4.75 mm modified recycled aggregate, 3 parts of cement, 3 parts of phosphogypsum, 2 parts of water, 4 parts of microcapsules, and 1 part of water reducer.
[0067] 5) Mix the raw materials prepared in step 4) evenly to obtain a mixture, then mold the mixture in a mold and cure it in an environment with a temperature of 30 °C and a humidity of 99% for 28 d to obtain the permeable mortar.
[0068] Comparative Example 1: Sodium metasilicate was not used in this comparative example, and other steps were the same as in Example 1.
[0069] Comparative Example 2: Aluminum sulfate was not used in this comparative example, and other steps were the same as in Example 1.
[0070] Comparative Example 3: Microcapsules were not used in this comparative example, and other steps were the same as in Example 1.
[0071] II. Performance Verification
[0072] 1. Test the performance of the permeable mortar prepared in Examples 1 - 6 and Comparative Examples 1 - 3 respectively according to the conventional method, and the results are shown in Table 1.
[0073] Table 1
[0074]
[0075] As can be seen from Table 1, compared with the comparative example, the later strength and water permeability coefficient of the permeable mortar prepared by the present invention have been significantly improved. After 15 cycles of freeze-thaw, the loss rates of strength and quality have decreased by about 68-93%, indicating that the permeable mortar of the present invention has excellent water permeability performance, high compressive strength and durability, and can thus improve the paving quality of ground materials such as permeable bricks. This is because the modified recycled aggregate added in the raw materials of the present invention has a stable pore structure and few microcracks, which improves the wrapping property and fluidity of the mortar, ensures uniform hydration, and at the same time makes the internal pores of the mortar more uniform, ensuring good water permeability. In addition, the controlled-release design of the microcapsules for the active components sodium metasilicate and aluminum sulfate ensures the continuous release of SiO2 and Al2O3 during the curing process, and through the organic combination with the hydration reaction of phosphogypsum, promotes the uniform distribution of C-S-H gel and ettringite, thereby optimizing the microstructure, improving the later mechanical strength and durability, and can extend the setting time, ensuring the construction performance. At the same time, the preparation process of the present invention is simple, effectively utilizes solid waste resources such as phosphogypsum and construction waste, is energy-saving and environmentally friendly, and is suitable for wide promotion and application.
[0076] The above are only the preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent replacements, and improvements made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A permeable mortar based on construction waste and composite phosphogypsum, characterized in that, It comprises the following raw materials in parts by weight: 4 - 8 parts of 1.18 - 2.36 mm modified recycled aggregate, 16 - 22 parts of 2.36 - 4.75 mm modified recycled aggregate, 2 - 4 parts of cement, 2 - 4 parts of phosphogypsum, 2 - 3 parts of water, 3 - 5 parts of microcapsules and 1 part of water reducing agent; The modified recycled aggregate is obtained by crushing and screening construction waste, followed by pickling, treatment with a surfactant, and then washing, drying and screening to the target particle size; The microcapsules have sodium metasilicate and aluminum sulfate as the core and polyvinyl alcohol, chitosan or sodium alginate as the wall.
2. The permeable mortar based on construction waste and composite phosphogypsum according to claim 1, wherein The mass ratio of sodium metasilicate to aluminum sulfate is 1.5 - 2.5:1; the molecular weight of the wall material is 80000 - 100000 Da.
3. The permeable mortar based on construction waste composite phosphogypsum according to claim 1, characterized in that, The mass ratio of the core to the wall is 4 - 8:
1.
4. The permeable mortar based on construction waste and composite phosphogypsum according to claim 1, wherein The surfactant is Tween-20 or Triton X-100; the pickling is carried out by immersing in dilute hydrochloric acid with a concentration of 1% - 3% for 5 - 10 min.
5. A method for preparing a permeable mortar based on construction waste and composite phosphogypsum according to any one of claims 1 to 4, characterized in that, It includes the following steps: 1) Construction waste is crushed, screened, washed, degreased and dried to remove the residual cement slurry and impurities on the surface, obtaining recycled aggregate with uniform particle size and clean surface; 2) The recycled aggregate obtained in step 1) is pickled, then placed in a surfactant for treatment, rinsed, dried, and finally two grades of aggregate with particle sizes of 1.18 - 2.36 mm and 2.36 - 4.75 mm are screened out, thus obtaining the modified recycled aggregate; 3) Dissolve the wall material in deionized water, heat and stir until completely uniform to obtain a polymer solution, then add sodium metasilicate and aluminum sulfate and stir at a low speed to make them uniformly dispersed, and then add an emulsifier under high-speed stirring to form a raw slurry containing active components. Drop the raw slurry into liquid paraffin and adjust the pH value of the system to 4.5 - 6.0, thus obtaining the microcapsules; 4) Weigh all the raw materials according to the parts by weight, mix them evenly to obtain a mixture, and then mold and cure the mixture to obtain the permeable mortar.
6. The preparation method of the permeable mortar based on construction waste and composite phosphogypsum according to claim 5, characterized in that, The construction waste can be selected from one or more of waste concrete, waste bricks or waste blocks.
7. The preparation method of the permeable mortar based on construction waste composite phosphogypsum according to claim 5, characterized in that, In step 2), the pickling time is 5 - 10 min, the treatment time in the surfactant is 5 - 15 min, and the drying temperature is 60 - 70 °C.
8. The preparation method of the permeable mortar based on construction waste and composite phosphogypsum according to claim 5, characterized in that, In step 3), the concentration of the polymer solution is 3 - 5 wt%; the emulsifier is Tween 80 or Span 80; the low-speed stirring speed is 300 - 500 rpm, and the high-speed stirring speed is 3000 - 4000 rpm.
9. The preparation method of the permeable mortar based on construction waste composite phosphogypsum according to claim 5, characterized in that, In step 4), the curing is carried out in an environment at 25 - 30 °C and a humidity of 95 - 100% for 28 - 30 d.
10. Application of the permeable mortar according to any one of claims 1 - 4 or the permeable mortar prepared by the method according to any one of claims 5 - 9 in the preparation of road materials.
Citation Information
Patent Citations
Bubble lightweight concrete bonding agent mortar composition and construction method thereof
CN102010178B
A permeable mortar for sponge cities and its preparation method
CN108328966B
Cited By
Reinforcing process and application of recycled concrete fine aggregate
CN121107732A